Financial statement
041-0111-001 SPANISH MEDICAL AID COMMITTEE President: Dr. CHRISTOPHER ADDISON Chairman: Dr. H.B. MORGAN Treasurers: Viscountess HASTINGS Professor MARRACK Viscount CHURCHILL Hon Secretary: Dr. CHARLES BROOK. L.C.C. 24 NEW OXFORD STREET W.C.1 Telephone: HOLborn 0605 Summarised Financial Statement. November 5th 1936 Receipts to date. 6,891. 10. 9. Surgical Equip. 1,192. 14. 6 General Equip. 1,434. 17. 8 Petty Cash A/c 533. 0. 0 Sundry Exs. 183. 18 3 Unit Expense A/c 2,328. 3. 9 Other Charges 1, 15. 2 5,674. 9. 6 Balance in Bank............ 1,217. 1. 3 £6,891. 10. 9. £ 6,891. 10. 9. Of the above balance £664. is tied up in respect of tryptiques. Accounts outstanding as per attached statement:- £1, 555. 5. 8 292/946/41/111